The Influence of Social Media on the Formation of Student Morals in the Digital Era - Ichsan Ichsan; La Iba; Muhammad Rajab; Zulfiah Larisu (Al-Ilmu, 2024)
This study aims to investigate the influence of social media use on the formation of students' morals in the digital era. The problem raised is how social media affects students' moral values and character. The method used in this study was a survey involving 60 respondents from among students. The results of the study showed that the use of social media has a significant and positive influence on the formation of students' morals, where the more often students use social media, the greater the impact on the development of their character and moral values. The conclusion of this study confirms that social media not only functions as a means of communication and entertainment, but also as a socialization agent that plays an important role in the development of students' character. The implications of these findings indicate the need for integration of digital literacy into the school curriculum, parental involvement in monitoring children's use of social media, and recommendations for policy makers to design regulations and educational programs that encourage healthy use of social media. Thus, the positive impact of social media on the formation of students' morals can be maximized, while its negative potential can be minimized.